Attualità sulle fratture periprotesiche di ginocchio - Melani, T.; Sani, G.; Carulli, C.; Innocenti, M. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC FRACTURES OF THE KNEE: AN UPDATE Periprosthetic fractures around the knee after arthroplasty represent a dramatic cause of revision, and their incidence is likely to rise in the next years as the number of Total Knee Arthroplasties will continue to increase. Our brief overview supports the fact that functional outcomes after periprosthetic fractures significantly decrease compared to the preinjury status, with a significant reduction in the mobility of patients. The treatment of periprosthetic knee fractures is extremely challenging and goes from a conservative treatment to open reduction and fixation and, finally, to implant of a megaprosthesis. Decision-making regarding the most appropriate treatment should be made on an individual basis depending on the location of fractures, stability of the components, and the age and functional requests of patients.